Le Statut Administratif de L’agent Public Contractuel dans la Fonction Publique Camerounaise (African Journal of Law and Politics, 2023)
The contract worker in Cameroon is regulated by the Labour Code, but worksfor the civil service, which is an administrative public service, he nce the question about his status. This status is administrative simply because the contract presents the jurisprudential criteria for administrative contracts, namely: the organic and functional criteria.